PROSES PENGEMBALIAN KERUGIAN NEGARA AKIBAT TINDAK PIDANA KORUPSI (Studi di Kejaksaan Negeri Medan) - Lesson Sihotang; Elsa Marlina Simalango (LPPM Universitas HKBP Nommensen, 2021)
To find out the process of recovering state losses in cases of corruption, and to find out the role of the prosecutor in the process of implementing state losses in cases of corruption as well as the obstacles to the process of recovering state losses due to corruption. And using the field method (field research), namely qualitative research by conducting direct research in the field to find out the existing problems through direct interviews with parties related to this research to obtain complete and accurate data. This results of the research that have been carried out are that the role of the Prosecutor in the implementation of returning state financial losses due to corruption through two instruments, the first is a criminal instrument, the second is a civil instrument. The implementation of the return of state losses due to corruption is carried out in a way, namely the Prosecutor's Office issues an order for the implementation of the decision (P48) to carry out the court's decision. Then the Prosecutor's Office reports each execution of the warrant in the Minutes of the Implementation of the Judge's Determination (BA-15). After completion, the Prosecutor's Office will send a letter of Implementation of the Determination of the Panel of Judges to the Head of the State Detention Center.